KOMPETENSI TEACHER LIBRARIAN DALAM KONSEP TEORI KOGNITIF SOSIAL (SELF EFFICACY) - Ernawati, Ernawati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Abstract The term teacher librarian (Teacher Librarian) is not widely known in Indonesia. The USA states that a Teacher Librarian is a teacher who has a background in librarianship. This brief article describes Teacher Librarian competency using a social theory approach, namely using the concept of Self Efficacy. There are four components that a Teacher Librarian must have, namely competence, management, education and technology. Although this competency is still not fully implemented in Indonesia. However, states like America have empowered TL as a way to develop libraries in the educational environment. Meanwhile, the concept of Self Efficacy itself is a tool in measuring a TL's ability to improve their performance and competence in accordance with the regulations applicable in their country. In contrast to Indonesia, the TL position itself is selected from teaching staff who serve as teachers with criteria and conditions set by the government even though in practice it does not match expectations and reality in the field. This article tries to provide an overview of Teacher Librarians and their presence in school libraries and uses Self Efficacy as a tool to measure one's qualities and abilities as a Teacher Librarian. Keywords: Competence, Teacher Librarian, Self Efficacy Abstrak Istilah guru pustakawan (Teacher Librarian) belum banyak dikenal di Indonesia. Negara USA menyebut Teacher Librarian adalah seorang pengajar (guru) yang memiliki latar belakang dalam keperpustakaan (librarianship). Artikel ringkas ini mendeskripsikan tentang kompetensi Teacher Librarian dengan pendekatan teori sosial yaitu menggunakan konsep Self Efficacy. Terdapat empat komponen yang harus dimiliki oleh Teacher Librarian yaitu kompetensi, manajemen, pendidikan dan teknologi. Meskipun kompetensi ini masih belum sepenuhnya terlaksana di Indonesia. Namun pada Negara bagian seperti Amerika telah memberdayakan TL ini sebagai salah satu pengembangan keberadaan perpustakaan dilingkungan pendidikan. Sedangkan konsep Self Efficacy sendiri menjadi salah satu alat bantu dalam mengukur kemampuan seorang TL dalam meningkatkan kinerja dna kompetensinya sesuai dengan ketentuan yang berlaku dinegaranya. Berbeda dengan Indonesia posisi TL sendiri dipilih dari tenaga pendidik yang menjabat sebagai guru dengan kriteria dan ketentuan yang ditetapkan oleh pemerintah meskipun pada prakteknya tidak sesuai harapan dan kenyataan dilapangan. Artikel ini mencoba memberikan gambaran tentang Teacher Librarian dan keberadaannya di perpustakaan sekolah serta menggunakan Self Efficacy sebagai alat bantu mengukur kualitas dan kemampuan diri sebagai Teacher Librarian. Kata Kunci : Kompetensi , Teacher Librarian, Self Efficacy